Benefits of cohort studies for child and adolescent health: Insights into substance use, the risk to mental health and potential transference possibilities in care provision Nutzen von Kohortenstudien zur Kinder- und Jugendgesundheit: Erkenntnisse über den Substanzkonsum, sein Risiko für die psychische Gesundheit und potenzielle Übertragungsmöglichkeiten in die Versorgung - Nees, Frauke; Eichler, Anna; Banaschewski, Tobias (Monatsschrift Kinderheilkunde, 2024)
Background: Longitudinal cohort studies are critical for understanding the development and course of mental disorders as well as their risk and protective factors, especially with respect to the substance use of parents and children, which can influence the development of psychological abnormalities. Objective: This article explains the significance of cohort studies in the context of parental (prenatal) and personal alcohol and cannabis use during childhood and adolescence as well as the impacts on mental and neurocognitive development into adulthood. Material and methods: A literature search was carried out in MEDLINE to select relevant studies. Results: Prenatal and early alcohol and cannabis use show predictive and long-term effects on mental health and neurocognitive development into early adulthood. Although many cohort studies exist, the evidence is limited and heterogeneous; however, the studies help to understand the influence of factors and to assess the specificity of the long-term consequences of substance use. Conclusion: Cohort studies offer unique insights into the development of health problems and their predictors. By utilizing existing datasets and conducting further investigations, insights can be maximized and integrated into prevention and intervention strategies through a coordinated and holistic response from various actors. This requires a joint commitment at the individual, familial, community and societal levels.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Alcoholic beverages; Cannabis; Mental health; Neurocognitive development; Pregnancy